The discretionary power of the judge in the determination of Ta’Zir punishment - Nasimah Hussin, (Fakulti Undang - Undang, 2004)

(untitled)
Ta’zir crime consists of all kinds of transgression where no specific and fixed punishment is prescribed. The judge is, in this case, authorised to inflict a punishment on the offender as he deems fit under the particular circumstances of the case. Since ta’zir punishment is subject to the discretion of the judge, the question arises as to whether this discretionary power is absolute or limited. Hence, this paper discusses the power of the judge in the determination of ta’zir punishment and the extent of which the judge has in exercising his discretion in determining punishments, are relevant to the topic and will also be discussed